PECULIARITIES OF TEACHING NATURAL SCIENCES AND STEM SUBJECTS IN PRIMARY SCHOOLS AT THE TURN OF THE XIX - XX CENTURIES (THE CASE OF THE URAL REGION) - Baishev, I.N. (Вестник Майкопского государственного технологического университета, 2023)
The relevance of the research is determined by the increasing importance of studying natural sciences and STEM subjects both in general and professional educational institutions, as well as the need to refer to the experience of building the educational process in Russia at the turn of the 19th - 20th centuries. The study of the content aspects of education and upbringing in pre-revolutionary Russia makes it possible to identify the priority tasks of the state policy in the field of education, to determine the place and role of the main academic disciplines in schools. The purpose of the research is to study the features of teaching Natural Sciences and STEM subjects in primary educational institutions of the Ural region within the specified chronological framework. The research objectives are to study the content of the curricula of elementary schools in pre-revolutionary Russia (the case of the Urals) on the basis of predominantly archival materials and scientific literature, to show the place and role of Natural sciences and STEM subjects, the features of their teaching and the factors that increase their importance in the educational process. The research methods are source study, historical and typological methods, comparative and historical methods. During the research, we have come to the following conclusions. Between the end of the 19th and the beginning of the 20th centuries there was a significant increase in the importance of studying the STEM subjects due to the dynamic economic growth of the country and the region we are considering, the strengthening of the applied nature of education in general, as well as the increased dependence of achieving success in life on the knowledge and skills acquired at school. In the primary educational institutions of the Ural region, there was a noticeable improvement in the methodological methods of teaching Natural sciences and STEM subjects. There was an active process of teaching children various crafts and agricultural work. In turn, the level of training and professional skills of teachers grew; there was a professional consolidation of teachers of primary and secondary educational institutions - teachers' communities arose and various congresses and forums were held.